DIMENSIONAL ACCURACY AS A RESULT OF CUTTING PARAMETERS AND MACHINE TOOL RIGIDITY IN DRY TURNING OF MEDIUM CARBON STEEL - Baharudin, A.B., Azureen, M.N., Rahman, M.A., Elfi, R.I.F., Dan M.M.P., (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Capability of machining processes is assessed by dimensional accuracy which is mentioned in main part of this paper as dimensional deviation. Part quality does not depend solely on the depth of cut (doc), feed rate (f) and cutting speed (v). Other variable such as excessive machine tool vibration due to low rigidity of machine tool can also affect the dimensional accuracy. The focus of the present study is to find a correlation between dimensional deviation against cutting parameters and machine tool vibration in a turning process. Hence cutting parameters and vibration-based regression model can be established for predicting the component dimensional accuracy. Experiments are conducted using a Computerized Numerical Control (CNC) lathe with carbide coated cutting tool insert. Vibration data is collected through a data acquisition system and then analyzed using statistical data analysis. The analysis revealed that machine tool vibration has significant effect on dimensional deviation where statistical analysis of individual regression coefficients showed p<0.05. The developed regression model has been validated through experimental tests and found to be reliable to predicting dimensional accuracy in dry turning process.